Strength diagnosis in elite Spanish clubs teams - Arrese, A. L.; Masia, J. R.; Izguierdo, D. M. (Journal of Human Sport & Exercise, 2009)
The article is about strength diagnostics in athletes in team sports such as handball, basketball, volleyball, fußball, futsal or hockey.